POSITIVISM AND ITS ADVERSARIES: BRADLEY, COLLINGWOOD, NIETZSCHE AND HEIDEGGER - Evaldas Nekrašas (Problemos)
The article deals with some aspects of positivism’s place in philosophy. The adversaries of positivism are distinguished from representatives of philosophical trends such as Marxism and pragmatism, which, like positivism, present themselves as scientific philosophies. Fighting for social progress under the same banner of science, they are allies of positivism, not enemies. Philosophers who disclaim that the scientific character of philosophy is the main indicator of its value may be regarded as adversaries of positivism. They belong to two main groups: members of the first group continue the philosophical tradition (mainly that of classical German philosophy) while representatives of the second group oppose the tradition but do so resting upon principles incompatible with those of positivists. In the article the former are represented by F. H. Bradley and R. G. Collingwood and the latter by F. Nietzsche and M. Heidegger. Among theoretical reproaches against positivism, the most convincing, it seems, is Collingwood’s claim that positivism does not comprehend the role of absolute (unverifiable and unappraisable in truth-terms) presuppositions of science and does not understand that the task of metaphysics is to detect such propositions, yet it seems that not all positivists are to be blamed for this. Relating positivism to thinkers attacking traditional metaphysics and belonging to the second group is quite a different task. For Nietzsche, positivism is a philosophy of the weak man. At the same time he believes that positivism excels all previous philosophies and is a step leading to his own philosophy. The relation of Heidegger to positivism is ambivalent as well. On the one hand positivism is for him the spiritual expression of the modern age, an essebtial element of modern civilisation. On the other hand, he regards positivism as a peculiar form of metaphysics and as such, to be overcome together with all metaphysics. It seems, however, that Heidegger’s hope that the character of world civilisation (which has been shaped by the positive, scientific world outlook) may radically change and a new civilisation capable of hearing the language of forgotten Being may be established has so far been proven futile. As a separate and integral trend of philosophy, positivism does not exist any longer. Its adversaries may interpret this fact as a victory, yet in the form of positive thought it remains at the heart of our civilisation. To overcome it once and for all without destroying the very foundations of our way of life and our evermore common culture is much more difficult than the most prominent critics may think.